Numerical analysis of inelastic reinforced high-strength concrete beams with low reinforcement ratio - Smarzewski, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2009)
Numerical modelling of flexural behavior of the reinforced highstrength concrete beams with low reinforcement ratio is discussed in this paper. Modelling mechanism of failure reinforced concrete beams under static load, static deformation processes of the reinforced high-strength concrete beams with regard to the physical nonlinearities of the structural materials (i.e. concrete and reinforcement steel) were developed using finite element analysis. The comparison of the numerical and experimental results as well as theoretical solutions, were presented. The compared results indicate correctness of the constitutive models of the structural materials: concrete and reinforcing steel and effectiveness of the solution method.